2010
DOI: 10.1097/ccm.0b013e3181d8cb51
|View full text |Cite
|
Sign up to set email alerts
|

Role of absolute lung volume to assess alveolar recruitment in acute respiratory distress syndrome patients

Abstract: Functional residual capacity is affected by PEEP. Ignoring this effect leads to relevant underestimation of alveolar recruitment as measure by pressure-volume curve displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…As for plateau pressure, this relationship could be demonstrated for the entire lung and, even more strongly, for the normally aerated tissue, suggesting that the smaller the ''baby lung'' receiving the tidal inflation, the more this will promote inflammation. This finding has potential clinical relevance because it supports the evidence (45,46) that, to set the appropriate VT, end-expiratory lung volume should be taken into account. In this study we used CT to measure end-expiratory lung volumes, whose measurements are in tight agreement with those obtained by bedside methods (15,47).…”
Section: Discussionsupporting
confidence: 67%
“…As for plateau pressure, this relationship could be demonstrated for the entire lung and, even more strongly, for the normally aerated tissue, suggesting that the smaller the ''baby lung'' receiving the tidal inflation, the more this will promote inflammation. This finding has potential clinical relevance because it supports the evidence (45,46) that, to set the appropriate VT, end-expiratory lung volume should be taken into account. In this study we used CT to measure end-expiratory lung volumes, whose measurements are in tight agreement with those obtained by bedside methods (15,47).…”
Section: Discussionsupporting
confidence: 67%
“…However, we must point out that the physiologic method used in the current study to estimate alveolar recruitment 36,37 has been shown to underestimate alveolar recruitment in some instances (see below for the limitations). 43 Interestingly, we document that the open lung strategy decreased E CW . To explain this result, we speculate that PEEP, applied after the RM, at least partially counterbalanced the diaphragm cranial shift induced by pneumoperitoneum and Trendelenburg position and that the corresponding lung expansion lead to a more physiologic chest wall shape leading to the observed reduction in E CW .…”
Section: Discussionmentioning
confidence: 94%
“…Although our data show that such strategy resulted in significant alveolar recruitment and improvement in lung mechanics, we must point out that the PEEP level applied in our study was likely inadequate to maximize alveolar recruitment. As we discussed above, tailoring PEEP to optimize alveolar recruitment is an important issue that deserves further studies; (5) to estimate open lung strategy-induced alveolar recruitment, we used the method originally proposed by Ranieri et al 36 We point out that although this method is useful to indicate that recruitment occurred, it may fail to precisely estimate the amount of alveolar recruitment in some instances, as recently shown by Patroniti et al 43 We acknowledge this as a limitation of our study; and (6) the FloTrac/Vigileo has not been thoroughly validated in the surgical context and furthermore is validated to monitor the trend of cardiac output rather than its absolute values. 33,44 In conclusion, we document the physiologic effects of a ventilatory strategy aiming at reversing pneumoperitoneuminduced alveolar collapse in patients with normal lung function undergoing laparoscopic surgery in Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%
“…From a technical standpoint, Patroniti et al [30] suggested that the method used to estimate the PEEP volume above FRC with PEEP (long exhalation to ZEEP) may underestimate recruitment because the true FRC may be modified after the use of high PEEP. Therefore, our method might have slightly underestimated recruitment.…”
Section: Discussionmentioning
confidence: 99%